2004
DOI: 10.1007/s10340-004-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Buprestidae (Coleoptera) community with successional age after fire in a Pinus brutia forest

Abstract: Fire is a frequent and common disturbance factor in Mediterranean ecosystems. It is a most spectacular ecological force because it destroys ecosystems in a very short time. Pinus brutia Ten. forests, which are one of the most widespread ecosystems in the eastern Mediterranean rim, have developed adaptations against fire. The adaptations evolved by plant species have been studied extensively. However, the response of insects, which are an important part of the ecosystem, has received little attention. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In addition, species that are both cavity nesters and bark insectivores (e.g., woodpeckers) could be positively impacted by increased nesting site availability, but negatively impacted in the short-term by reduced food resource availability. Wood-boring beetles often increase dramatically within 1-2 years following forest fires (Kaynas and Gürkan, 2005;Boulanger and Sirois, 2007), and thus abundance of cavity nesters and bark insectivores could increase substantially in the next few years. Bagne and Purcell (2011) found that bark insectivores began to increase three to six years after prescribed burning in California.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, species that are both cavity nesters and bark insectivores (e.g., woodpeckers) could be positively impacted by increased nesting site availability, but negatively impacted in the short-term by reduced food resource availability. Wood-boring beetles often increase dramatically within 1-2 years following forest fires (Kaynas and Gürkan, 2005;Boulanger and Sirois, 2007), and thus abundance of cavity nesters and bark insectivores could increase substantially in the next few years. Bagne and Purcell (2011) found that bark insectivores began to increase three to six years after prescribed burning in California.…”
Section: Discussionmentioning
confidence: 99%